Interaction between calcium and slow channel blocking drugs on atrial rate - Camilión de Hurtado, María Cristina (1983)
The relationship between extracellular calcium concentration and the chronotropic effect of prenylamine, verapamil and nifedipine was studied in isolated spontaneously beating rat atria. The three slow channel blocking drugs produced a concentration-dependent decrease in atrial rate, though with different relative potencies. The order of potency for decreasing atrial rate, independently of the calcium level (1.0, 3.0, 6.0 or 9.0 mmol/l) was: verapamil > nifedipine > prenylamine. Increasing calcium from 1.0 to 6.0 and 9.0 mmol/l increased atrial rate from 251±beats·min−1 to 265±6 beats·min−1 and 285±9 beats·min−1 (mean±1 standard error) respectively (P<0.05). Despite their positive chronotropic effect high calcium levels failed to reverse the negative chronotropic effect of the slow channel blockers. Furthermore, the negative chronotropic effect of both verapamil and nifedipine was enhanced at high calcium levles. Raising calcium from 1.0 to 6.0 mmol/l in the presence of verapamil (1×10−7 mol/l) or nifedipine (3×10−7 mol/l) increased 2-fold the negative chronotropic effect of the calcium channel blockers. In addition, the concentration-effect curves for verapamil and nifedipine shifted to the left by 0.50±0.14 and 0.50±0.16 log units, respectively, when calcium increased from 1.0 to 6.0 mmol/l.